Characterisation and comparison of semen microbiota and bacterial load in men with infertility, recurrent miscarriage, or proven fertility - Shahriar Mowla; Linda Farahani; Tharu Tharakan; Rhianna Davies; Goncalo DS Correia; Yun S Lee; Samit Kundu; Shirin Khanjani; Emad Sindi; Raj Rai; Lesley Regan; Dalia Khalifa; et al. (eLife)
Several studies have associated seminal microbiota abnormalities with male infertility but have yielded differing results owing to their limited sizes or depths of analyses. The semen microbiota during recurrent pregnancy loss (RPL) has not been investigated. Comprehensively assessing the seminal microbiota in men with reproductive disorders could elucidate its potential role in clinical management. We used semen analysis, terminal-deoxynucleotidyl-transferase-mediated-deoxyuridine-triphosphate-nick-end-labelling, Comet DNA fragmentation, luminol reactive oxidative species (ROS) chemiluminescence, and metataxonomic profiling of semen microbiota by 16S rRNA amplicon sequencing in this prospective, cross-sectional study to investigate composition and bacterial load of seminal bacterial genera and species, semen parameters, ROS, and sperm DNA fragmentation in men with reproductive disorders and proven fathers. 223 men were enrolled, including healthy men with proven paternity (n=63), the male partners in a couple encountering RPL (n=46), men with male factor infertility (n=58), and the male partners of couples with unexplained infertility (n=56). Rates of high sperm DNA fragmentation, elevated ROS, and oligospermia were more prevalent in the study group compared with control. In all groups, semen microbiota clustered into three major genera-dominant groups (1, Streptococcus; 2, Prevotella; 3, Lactobacillus and Gardnerella); no species clusters were identified. Group 2 had the highest microbial richness (p<0.001), alpha-diversity (p<0.001), and bacterial load (p<0.0001). Overall bacterial composition or load has not been found to associate with semen analysis, ROS, or DNA fragmentation. Whilst global perturbation of the seminal microbiota is not associated with male reproductive disorders, men with unidentified seminal Flavobacterium are more likely to have abnormal seminal analysis. Future studies may elucidate if Flavobacterium reduction has therapeutic potential.